2009
DOI: 10.1007/s10600-010-9506-8
|View full text |Cite
|
Sign up to set email alerts
|

Apolar constituents of some biologically active Dianthus species from Western Anatolia

Abstract: The apolar constituents of four Dianthus (Caryophyllaceae) species were determined by GC-MS. Palmitic, linoleic, and oleic acids were detected as dominant components in all species. D. elegans d′Urv. var. elegans had the highest antioxidant activity. All four species also showed considerable antimicrobial activity against S. epidermidis and C. albicans. Dianthus L. (Caryophyllaceae) is a genus of about 300 species in the world, distributed in the Mediterranean Region and in the Middle East [1]. In Turkey, 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…96, 13.35, 9.86, 9.45, 7.68, 2.65 and 1.55% of total fatty acids, respectively. These results are in agreement with previous reports stating the fatty acid compositions of different higher plants of the same family [2][3][4].…”
supporting
confidence: 94%
See 1 more Smart Citation
“…96, 13.35, 9.86, 9.45, 7.68, 2.65 and 1.55% of total fatty acids, respectively. These results are in agreement with previous reports stating the fatty acid compositions of different higher plants of the same family [2][3][4].…”
supporting
confidence: 94%
“…96, 13.35, 9.86, 9.45, 7.68, 2.65 and 1.55% of total fatty acids, respectively. These results are in agreement with previous reports stating the fatty acid compositions of different higher plants of the same family [2][3][4].The total of 17 subfractions from the dichloromethane fraction was characterized by the presence of a high proportion of saturated fatty acids (SFAs) with a value of 73.01%, followed by polyunsaturated fatty acids (PUFAs) and monounsaturated fatty acids (MUFAs), representing 17.53 and 7.46%, respectively.Linoleic and linolenic acids were determined as 17.54% of all subfractions. With regard to omega 3, subfraction 3 had the highest amount (23.20 r 0.51%).…”
supporting
confidence: 92%
“…var. zonatus were also mentioned that they mainly consist of terpenes, essential fatty acids, and volatile compounds (Durucasu et al, 2009). Comparing the present data (Table 1) with those previously reported in literature, the study of essential oils shown different chemical profiles in each Dianthus species.…”
Section: Isolation Of the Essential Oilssupporting
confidence: 82%
“…Carnation flowers used as expectorant syrup. The essential oil of Dianthus L. genus were commonly used in serums, creams and massage oil and they have various biological activities such as; antispasmodic, cardiotonic, diaphoretic, nervine, anxiety, antidepression, analgesic, diuretic, antihepatotoxic, and dermatologic (Ibrahim, 2016;Tisserand and Young, 2014;Chevallier, 1996;Chopra et al, 1986;Durucasu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation